2012
DOI: 10.1021/nn302729j
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Switching of the Epitaxial Graphene–Metal Interaction

Abstract: Using photoemission spectroscopy techniques, we show that oxygen intercalation is achieved on an extended layer of epitaxial graphene on Ir(111), which results in the "lifting" of the graphene layer and in its decoupling from the metal substrate. The oxygen adsorption below graphene proceeds as on clean Ir(111), giving only a slightly higher oxygen coverage. Upon lifting, the C 1s signal shows a downshift in binding energy, due to the charge transfer to graphene from the oxygen-covered metal surface. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
241
6
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(287 citation statements)
references
References 50 publications
(103 reference statements)
29
241
6
11
Order By: Relevance
“…After Gr growth, the Gr-alloy interface was exposed to a high flux of molecular oxygen (pressure ¼ 3 Â 10 À 3 torr) at 520 K. Following this procedure, it is possible to intercalate oxygen underneath the Gr layer and to selectively oxidize only the Al atoms at the metal interface. In fact, the intercalation of noble or light atoms has already proven to be an effective method to create an interface nanosheet between Gr and the substrate [21][22][23][24] . Figure 3a,b shows a set of high-resolution photoemission spectra acquired after different oxygen exposures, for the C1s and Al2p levels, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After Gr growth, the Gr-alloy interface was exposed to a high flux of molecular oxygen (pressure ¼ 3 Â 10 À 3 torr) at 520 K. Following this procedure, it is possible to intercalate oxygen underneath the Gr layer and to selectively oxidize only the Al atoms at the metal interface. In fact, the intercalation of noble or light atoms has already proven to be an effective method to create an interface nanosheet between Gr and the substrate [21][22][23][24] . Figure 3a,b shows a set of high-resolution photoemission spectra acquired after different oxygen exposures, for the C1s and Al2p levels, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to underline the absence of any interfacial buffer layer between Gr and alumina, which would give rise to a feature at 281.5 eV (the BE corresponding to the Al-C bonds) and 282.5 eV (Al-O-C bond) 28,29 and also to C-O bonds characteristic of epoxy, ethers, quinones and lactones, which typically show up in the C1s spectrum at binding energies4284.2 eV (ref. 22). In addition, we can safely rule out the formation of a high density of Gr defects such as single-and double-vacancies or Stone-Wales defects.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, in Ref. [37] authors showed that intercalation of oxygen leads to decoupling of graphene from the substrate with the shift of the Dirac point by 0.57 eV above the Fermi level. On the other hand, Cu intercalated graphene on Ir(111) is characterized by a gap between the π and π * states, opened by lifting the sublattice symmetry due to hybridization of the Cu and graphene bands [38].…”
Section: Discussionmentioning
confidence: 99%
“…27,[32][33][34] The intercalated oxygen atoms directly attack carbon atoms inside graphene islands with high oxidation rate. 27 On graphene/Ir(111) surfaces oxygen intercalation is also feasible in low pressure O 2 , 30,35 and the mechanism of direct attack by the intercalated oxygen atoms is active for the graphene oxidation. Moreover, wrinkles are present at the graphene/Ir(111) surfaces, 14,15 which probably make the oxygen intercalation easier and enhance the oxidation as well.…”
mentioning
confidence: 99%